Impact of Diabetes Mellitus on Outcomes in Patients Supported With Left Ventricular Assist Devices: A Single Institutional 9-Year Experience. (November 2017) - Asleh, Rabea; Briasoulis, Alexandros; Schettle, Sarah D.; Tchantchaleishvili, Vakhtang; Pereira, Naveen L.; Edwards, Brooks S.; Clavell, Alfredo L.; Maltais, Simon; Joyce, David L.; Joyce, Lyle D.; Daly, Richard C.; Kushwaha, Sudhir S.; et al.
Abstract : Background: Diabetes mellitus (DM) is a risk factor for morbidity and mortality in patients with heart failure. The effect of DM on post–left ventricular assist device (LVAD) implantation outcomes is unclear. This study sought to investigate whether patients with DM had worse outcomes than patients without DM after LVAD implantation and whether LVAD support resulted in a better control of DM. Methods and Results: We retrospectively reviewed 341 consecutive adults who underwent implantation of LVAD from 2007 to 2016. Patient characteristics and adverse events were studied and compared between patients with and without DM. One hundred thirty-one patients (38%) had DM. Compared with patients without DM, those with DM had higher rates of ischemic cardiomyopathy, LVAD implantation as destination therapy, and increased baseline body mass index. In a proportional hazards (Cox) model with adjustment for relevant covariates and median follow-up of 16.1 months, DM was associated with increased risk of all-cause mortality (hazard ratio, 1.73; 95% confidence interval: 1.18–2.53; P =0.005) and increased risk of nonfatal LVAD-related complications, including a composite of stroke, pump thrombosis, and device infection (hazard ratio, 2.1; 95% confidence interval: 1.35–3.18; P =0.001). Preoperative hemoglobin A1c was not significantly associated with mortality or adverse events among patients with DM. LVAD implantation resulted in a remarkable decrease in hemoglobin A1c levels (7.4±1.9 pre-LVAD versus 6.0±1.5 and 6.3±1.4 after 3 and 12 months post-LVAD, respectively; P <0.0001) and a significant reduction in requirements of DM medications. Conclusions: DM is associated with increased rates of all-cause mortality and major adverse events despite favorable glycemic control after LVAD implantation.